ANALYSIS OF PRE-HOSPITAL TREATMENT OF ACUTE CORONARY SYNDROME - O. V. Reshetko; R. M. Magdeev; N. V. Furman (Рациональная фармакотерапия в кардиологии, 2015)
Aim. To evaluate the pre-hospital treatment of patients with acute coronary syndromes (acute myocardial infarction and unstable angina) in 2001 and 2006. Material and methods. Retrospective pre-hospital treatment survey was performed in 1114 patients with acute coronary syndrome (acute myocardial infarction (AMI) or unstable angina (UA)) in 2001 and 2006. Results. For acute myocardial infarction use of aspirin, β-blockers, heparin was 0%, 0%, 81,5% in 2001 and 23,9%, 8%, 13,4% in 2006, respectively. Use of aspirin, β-blockers, heparin in unstable angina were 0%, 16,2%, 12,3% in 2001 and 3,4%, 1,6%, 0,5% in 2006, respectively. Fibrinolytic therapy was not provided. Polypragmasia reduced in 2006 in comparison with 2001. Conclusions. This survey demonstrates the discordance between existing current practice and guidelines for acute coronary syndrome.